Factors affecting construction costs in affordable housing for low-income group in Sana'a, Yemen - Mohammed Alaghbari, Wa'el Abdulmoghni (2010)
Yemen is one developing country in the Middle East, which suffers from housing shortage. Unprecedented rapid urban growth coupled with lack of infrastructure has led to the problem of housing shortage for the low-income group in Sana’a, the capital city of Yemen. Consequently, informal housing patterns are observed clearly in some sectors of the city. The low-income group has built this kind of housing urgently and in some cases immediately as the final and only solution, yielding serious implications on the quality and safety of the houses. The overriding objective of this study was to identify the significant factors, which have influenced the construction cost of housing in Sana’a to resolve the housing shortage for the low-income group. Specific objectives have included determining the factors causing housing shortage for low-income group in Sana’a; justifying the significant factors influencing the cost of low-cost housing; and recommending to relevant authorities in Yemen to improve housing policies to mitigate the housing shortage in Sana’a. An important contribution of this study is the analysis of the construction cost of housing for the first time through the use of the Hedonic Regression Model (HRM). Two different survey questionnaires were used to achieve the study objectives. The first was to examine the requirements of low-income group, while the second was to analyze the feedbacks from professionals attached to relevant housing agencies in Sana’a. Statistical analyses using the descriptive statistics - Chi- Square tests, T-tests, ANOVA,and HRM analysis were carried out to study the difference in the variables used. HRM for housing was developed and used to analyze the physical characteristics of location;characteristics of building - materials, finishing works and construction methods; and other external factors related to the choice of these characteristics. This study has concluded that most householders were not satisfied with the quality of houses and associated services. They preferred to own new houses but could not afford to do so as obtaining financial assistance or loans have been difficult. In this context,the study has determined that the households wanted to get housing loan with at least 25 years installments. The analysis of professionals’ questionnaire has concluded that the significant factors causing the shortage of low-cost housing were high cost of housing,poor handling of available economic resources, lack of legislation policy on housing,and lack of organization and co-ordination of activities related to housing. Reinforced concrete frame structure was regarded as the best construction method and concrete blocks for internal and external walls as the best materials to build low-cost housing in Sana’a. Significant factors affecting construction cost of housing in Sana’a included cost of land, cement and steel. Other factors influencing the shortage of low cost housing included economic condition and uncertainly in foreign exchange,construction materials availability in the market, and unstable political situations. The most important factor, related to construction method, and could also affect the construction cost of housing in Sana’a, was the concrete frame structure. This study has significantly contributed to the housing industry. Firstly, it has employed HRM as a new tool in the field of housing economic to analyze cost of housing characteristics. Secondly, it has formulated valuable housing policies to be implemented by authorities in Yemen.